Effect of midgut proteolytic activity on susceptibility of lepidopteran larvae to Bacillus thuringiensis subsp. Kurstaki - Talaei-Hassanloui, Reza; Bakhshaei, Raziyeh; Hosseininaveh, Vahid; Khorramnezhad, Ayda (Frontiers in Physiology, 2014)
Bacillus thuringiensis (Bt) is the most effective microbial control agent for controlling numerous species from different insect orders. All subspecies and strains of B. thuringiensis can produce a spore and a crystalline parasporal body. This crystal which contains proteinaceous protoxins is dissolved in the alkaline midgut, the resulting molecule is then cleaved and activated by proteolytic enzymes and acts as a toxin. An interesting aspect of this activation process is that variations in midgut pH and protease activity have been shown to account for the spectrum of some Bt proteins activity. Thus, an important factor that could be a determinant of toxin activity is the presence of proteases in the midgut microenvironment of susceptible insects. Reciprocally, any alteration in the midgut protease composition of the host can result in resistance to Bt. Here in this paper, we reviewed this processes in general and presented our assays to reveal whether resistance mechanism to Bt in Diamondback Moth (DbM) larvae could be due to the function of the midgut proteases? We estimated LC50 for both probable susceptible and resistant populations in laboratory and greenhouse tests. Then, the midgut protease activities of the B. thuringiensis induced-resistant and susceptible populations of the DbM were assayed on Hemoglubin and on N-alpha-benzoyl-DL-arginine-p-nitroanilide (BapNA) for total and tryptic activities, respectively. Six hours after feeding on Bt treated and untreated canola leaves, the midguts of instar larvae of both populations were isolated. Following related protocols, peptides released through the activity of proteinases on Hemoglubin and BApNA were recorded using microplate reader. Control (Blank) was also considered with adding TCA to reaction mix before adding enzymatic extract. Data analysis indicated that there are significant differences for tryptic activity on BApNA and also for total proteolytic activity on Hemoglubin between susceptible and resistant populations fed on Bt treated leaves. But these differences were not significant for larvae fed on healthy canola leaves between these two populations. These results which supported the role of DbM's proteolytic system in development of resistance to Bt, will be discussed in details.